SHORT NOTES ON LASER AND THIER MILITARY APPLICATIONS - Taylor, A (Scientia Militaria - South African Journal of Military Studies, 2012)
In this age of rapid technological achievement, most people have heard of lasers, but most keep a respectful distance, acknowledging humbly that such a topic is the inalienable domain of the scientist. Few know what lasers actually are.